Incident arrhythmias in relation to ventilatory parameters and pulmonary disease: evidence from two prospective cohort studies - Yun-Jiu Cheng; Li-Ping Qu; Yi-Jian Liao; Si-Long Lu; Mei-Ping Lin; Qian He; Jin-Bo Fu; Jun-Chi Li; Wen-Juan Duan; Li-Juan Liu (BMC Medicine)
Abstract Background Emerging epidemiological evidence implicates pulmonary dysfunction in cardiovascular pathogenesis, yet its arrhythmogenic potential remains poorly defined. Objectives We aimed to assess the link between ventilatory parameters, pulmonary disease phenotypes and risk of incident arrhythmias across diverse populations. Methods We analyzed data from 17,684 adults in two prospective cohort studies-the Atherosclerosis Risk in Communities (ARIC; n = 12,929) and Cardiovascular Health Study (CHS; n = 4,755). Adjudicated arrhythmia diagnoses (atrial fibrillation/flutter [AF/AFL], ventricular arrhythmias [VAs], high-grade atrioventricular [AV] block, and premature atrial/ventricular complexes [PAC/PVC]) were identified via hospitalization records and mortality data. Multivariable-adjusted Cox proportional hazards models quantified associations between forced expiratory volume in 1 s (FEV1%) predicted and forced vital capacity (FVC%) predicted quartiles with arrhythmia risk, adjusting for traditional cardiovascular risk factors. Results Over a median follow-up of 12.6 years, impaired FEV1% and FVC% corresponded to a graded increase in arrhythmia risk. Compared to the highest quartile, the lowest FEV1% predicted quartile had elevated hazards for any arrhythmias (HR 1.32, 95% CI 1.23–1.42), AF/AFL (HR 1.68, 1.52–1.85), VAs (HR 1.55, 1.29–1.86), high-grade AV block (HR 1.37, 1.08–1.73), and PAC/PVC (HR 1.42, 1.20–1.69). Similar trends were observed for FVC% predicted quartiles. These associations remained consistent in never-smoking individuals and across cohorts. Obstructive spirometry pattern was associated with the strongest arrhythmia risk, while restrictive ventilatory patterns showed relatively lower risk elevations. No association was observed with sick sinus syndrome. Conclusions Reduced pulmonary function suggested independent associations with incident arrhythmias across supraventricular, ventricular, and conduction system pathologies in two historical cohorts. These findings suggest that spirometric indices could potentially represent novel independent indicators for arrhythmia development worthy of further validation in contemporary settings,, with associations distinct from conventional cardiometabolic risk factors.